Identification of shallow groundwater potential areas in Thuthappuzha sub - basin using GIS technology - ABDUL SUHAIL; Chithra M. G; Deepthy C; Jiji P. S; Er. Anu Varughese (Guide) (Tavanur 2011 Kelappaji College of Agricultural Engineering and Technology)
Identification of shallow groundwater potential areas in Thuthappuzha sub - basin using GIS technology
Identification of shallow groundwater potential areas in Thuthappuzha sub - basin using GIS technology